Resistência à compressão dos concretos usados na região metropolitana do Recife: conformidade e análise estatística. - Aguiar, Roberto de Castro (2018)
Compressive strength is the most important and desirable property of a concrete. In this way, problems of nonconformity in the values of the compressive strengths are configured in a reduction of the quality of the concrete, consequently in the reduction of its durability and useful life, besides a risk to the structural safety. The general objective of this research is to know, through quantitative data, the performance of concrete used in the construction of residential, commercial and business buildings built in the metropolitan region of the city of Recife (RMR). In addition, to classify individually the works by the concept of the Global Lot, that is to say, by the percentage of nonconformity of all its concretes; compare the compliances between machined concretes and "in loco"; verify the conformity and the annual evolution of the concretes by resistance classes; and to determine proper characteristics of the use of the concrete by the RMR works. A field research was used as methodology, where the 8 main RMR contractors authorized the supply of the results of resistance to compression at 28 days of some of their works, through a single laboratory of materials accredited to the Brazilian Network of Testing Laboratories (RBLE). A total of 235 complete works were analyzed, and 122,810 representative copies were processed in electronic spreadsheet, of which 1,308 were produced "locally" and 121,502 produced by 9 concrete plants, of which 8 were produced nationally. The percentage of total nonconformity of concretes was found in 20.21% for concrete in situ in 37.84% and for concretes machined in 20.02%. Of the 235 works, only 6 (2.6%) obtained their total percentage of non-conforming results of less than or equal to 5%, consequently, 229 works (97.4%) obtained total percentages of nonconforming results greater than 5% , of which, of these 229 works, 110 (46.8%) obtained total percentages of non-conforming results greater than 20%. It is concluded that the disregard with the dosing strength yields 1 nonconforming batch for every 20 batches evaluated, representing a quantity 400% greater than that determined by NBR 6118/2014.